The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7554/elife.00691
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-mediated PTEN conformational closure and deactivation revealed with protein semisynthesis

Abstract: The tumor suppressor PIP3 phosphatase PTEN is phosphorylated on four clustered Ser/Thr on its C-terminal tail (aa 380–385) and these phosphorylations are proposed to induce a reduction in PTEN’s plasma membrane recruitment. How these phosphorylations affect the structure and enzymatic function of PTEN is poorly understood. To gain insight into the mechanistic basis of PTEN regulation by phosphorylation, we generated semisynthetic site-specifically tetra-phosphorylated PTEN using expressed protein ligation. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 65 publications
(106 reference statements)
7
138
0
Order By: Relevance
“…5A). To verify this, we used limited proteolysis, which is a wellcharacterized technique used to measure changes in the conformational stability and flexibility of proteins (54). Digestion of the purified ectodomain of nicastrin with varying amounts of trypsin in the presence or absence of reducing reagent revealed that reduced nicastrin was substantially more sensitive to proteolysis than the unreduced protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A). To verify this, we used limited proteolysis, which is a wellcharacterized technique used to measure changes in the conformational stability and flexibility of proteins (54). Digestion of the purified ectodomain of nicastrin with varying amounts of trypsin in the presence or absence of reducing reagent revealed that reduced nicastrin was substantially more sensitive to proteolysis than the unreduced protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 In addition, binding of PTEN with the plasma membrane is also regulated by the phosphorylation status of PTEN. [16][17][18] This interaction is delineated in more detail in the following sections.…”
Section: Pten and Tumor Suppressionmentioning
confidence: 99%
“…33 In addition, Tyr240 and Tyr315 phosphorylation could help to maintain phosphatase function of PTEN. 34,35 Bolduc et al 16 found that upon phosphorylation of the 380-385 Ser/Thr cluster, the PTEN C-terminal modified tail clamps down intramolecularly on the C2 domain, preventing PTEN from binding to the plasma membrane and reducing its catalytic action toward PIP3. Nguyen also proved that the phosphatase catalytic site forms the membrane-binding regulatory interface and interacts with the inhibitory phosphorylated C-terminal tail.…”
Section: Regulation Of Pten Functionsmentioning
confidence: 99%
“…A cluster of serine and threonine residues (Ser380, Thr382, Thr383 and Ser385) in the regulatory C-terminal tail of PTEN is constitutively phosphorylated by casein kinase 2 (CK2). This results in a stable 'closed' form that has reduced lipid phosphatase activity, decreased plasma membrane targeting and increased conformational compaction [15][16][17][18][19] . Intramolecular interaction of the phosphorylated C-terminal tail with basic residues within the N-terminal PIP2-binding motif, the catalytic and C2 domains, maintains PTEN in its 'closed' form 20,21 .…”
mentioning
confidence: 99%
“…Mutation of the C-terminal tail phosphorylation cluster disrupts the intramolecular interaction and promotes an 'open' form of PTEN with increased catalytic activity and plasma membrane targeting. These findings have led to an elegant model whereby a phosphorylation-regulated switch controls the transition of PTEN from a 'closed' cytoplasmic inactive state and an 'open' active state that is localized to the plasma membrane 17,19,21 . PTEN is also phosphorylated in its C2 domain by ROCK, the downstream effector of RhoA, resulting in increased PTEN catalytic activity 22 .…”
mentioning
confidence: 99%